The Consequence Of Dividend Payout On Profitability: An Investigation Study On Pharmaceutical Industry In India - M S , KOKILA; SATYA, DR.KALANJERI VENKATESH; CHOUDHURY, PRASANT KUMAR (The journal of contemporary issues in business and government, 2021)
The main aim of this study is to establish the relationship between dividend payout and firms profitability among the top Pharmaceutical Companies operating in India. Secondary data is used for carrying out the present study. Statistical techniques like correlation and multiple regression analysis were applied for analyzing the data. The major findings based on the results of Cipla showed a significant relationship between profitability and dividend payout and the remaining companies showed insignificant result. But in the statistical tool correlation analysis, majority of the Pharmaceutical Company taken for the study showed a strong positive correlation between dividend profitability and dividend payout. The major conclusion is inferred from this study that there is a relevancy in the dividend payout and firms profitability that improves the shareholders wealth.